Emission and control of N2O and composition of ash derived from cattle manure combustion using a pilot-scale fluidized bed incinerator. Issue 4 (16th February 2016) - Oshita, Kazuyuki; Kawaguchi, Koji; Takaoka, Masaki; Matsukawa, Kazutsugu; Fujimori, Takashi; Fujiwara, Taku
Abstract : This study investigates the emission of nitrous oxide (N2 O) and discusses the reduction of N2 O emissions during the 24-h combustion of cattle manure using a pilot-scale fluidized bed incinerator under various experimental conditions. The results of these experiments were then validated against previously reported data. In addition, the characteristics of cattle manure incineration ash and their changes under different combustion conditions were estimated. In incineration experiments with composted cattle manure, N2 O concentrations using multi-stage combustion were 75% lower than the concentrations resulting from normal combustion without additional auxiliary fuel, since N2 O could be decomposed in the high-temperature zone formed by the inlet of the secondary combustion air. The N2 O emission factor under normal combustion conditions (800°C) was 6.0% g-N2 O-N/g-N. This result is similar to the values found in previous studies at the same temperature. The N2 O emission factor was decreased to 1.6% g-N2 O-N/g-N using a multi-stage combustion procedure. The current Japanese N2 O emission factor of 0.1% g-N2 O-N/g-N is an underestimate for some conditions and should be uniquely specified for each condition. Finally, cattle manure ash contains ample fertilizer elements, little Fe, Al and Zn, but abundant Cl. Therefore if Cl could be removed by some kind of pretreatment, cattle manure ash could be used as a favourable fertilizer.